2008
DOI: 10.1093/bja/aen020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine premedication on the intraocular pressure changes after succinylcholine and intubation

Abstract: We conclude that dexmedetomidine could be a beneficial premedication in open globe injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
48
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 24 publications
14
48
1
1
Order By: Relevance
“…before induction as a premedicant blunted the rise in IOP caused by suxamethonium, laryngoscopy and endotracheal intubation. Our study correlates with the studies done by G Weigert (2007) 12 , Mowafi (2008) 7 and Pal CK (2011) 8 , as in all of their studies there is a reduction in IOP in dexmedetomidine and clonidine Groups at various time intervals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…before induction as a premedicant blunted the rise in IOP caused by suxamethonium, laryngoscopy and endotracheal intubation. Our study correlates with the studies done by G Weigert (2007) 12 , Mowafi (2008) 7 and Pal CK (2011) 8 , as in all of their studies there is a reduction in IOP in dexmedetomidine and clonidine Groups at various time intervals.…”
Section: Discussionsupporting
confidence: 92%
“…It has been observed that the rise of IOP with suxamethonium and intubation can be blunted with dexmedetomidine premedication. 7 In the year 2014, Shalini et al 8 concluded that dexmedetomidine premedication obtund the intraocular pressure rise after suxamethonium and endotracheal intubation. Aim of this study is to compare the effect of IV dexmedetomidine and IV clonidine premedication on the intraocular pressure changes haemodynamic responses after succinylcholine injection and intubation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence in our study we administered the bolus dose over 10 minutes. 15 The administration of the test drugs over 10 minutes in our study concurs with the studies conducted by Mowafi et al 10 Basar et al 12 and Kunisawa et al 4 …”
Section: Methods Of Administrationsupporting
confidence: 92%
“…The decrease in mean MAP observed at 1 st , 5 th and 10 th minutes after intubation in group DX-0.6 and group DX-1 was statistically highly significant compared to same in group CT(p=0.000). DISCUSSION: Dexmedetomidine has been found by various authors [1][2][3][4][5][10][11][12][13] to blunt the haemodynamic response for laryngoscopy and intubation. Different doses of Dexmedetomidine have been used to find the effectiveness for blunting haemodynamic responses to laryngoscopy and intubation, with conflicting results.…”
Section: Repeated Measure Anovamentioning
confidence: 99%
“…9,10 In 1989 Indu et al, suggested that sublingual nifedipine is effective in attenuating the IOP response after succinylcholine administration, laryngoscopy and intubation. 11 In 1993 Kelly et al, studied the effect of succinylcholine in 15 patients undergoing elective enucleation, after all the extraocular muscles were detached in the diseased eye to that of the normal eye that had the extraocular muscles attached. Baseline IOP was comparable in both eyes.…”
Section: Discussionmentioning
confidence: 99%